Extracellular Enzymes and Bioactive Compounds from Antarctic Terrestrial Fungi for Bioprospecting - Laura Zucconi; Fabiana Canini; Marta Elisabetta Temporiti; Solveig Tosi (International Journal of Environmental Research and Public Health, 2020)
Antarctica, one of the harshest environments in the world, has been successfully colonized by extremophilic, psychrophilic, and psychrotolerant microorganisms, facing a range of extreme conditions. Fungi are the most diverse taxon in the Antarctic ecosystems, including soils. Genetic adaptation to this environment results in the synthesis of a range of metabolites, with different functional roles in relation to the biotic and abiotic environmental factors, some of which with new biological properties of potential biotechnological interest. An overview on the production of cold-adapted enzymes and other bioactive secondary metabolites from filamentous fungi and yeasts isolated from Antarctic soils is here provided and considerations on their ecological significance are reported. A great number of researches have been carried out to date, based on cultural approaches. More recently, metagenomics approaches are expected to increase our knowledge on metabolic potential of these organisms, leading to the characterization of unculturable taxa. The search on fungi in Antarctica deserves to be improved, since it may represent a useful strategy for finding new metabolic pathways and, consequently, new bioactive compounds.